The electrodynamics of the Earth’s natural electromagnetic field - V. V. Aksenov (Известия высших учебных заведений: Геология и разведка)
The review of the published works on the electrodynamics of the present natural electromagnetic field that is observed on the Earth’s surface is suggested. We discuss the problems of applied geomagnetism which arise in the interpretation of the data of the two international geophysical years (IGY), that is, of 1933 and 1957/58 as well as of the data of the Word Magnetic Survey of 1964/65. This paper elaborates the results obtained in the authors previous papers that were published in 2012 in the journal «Geologia i Razvedka» in Discussions. The refinements have been made owing to grounds, suggested in those publication’s: grounds of the effects of Van-Vleuten-Benkova, Chetaev, Larmor, Maxwell’s equations for force and non-force fields.